Investor initiatives program: Public‐private partnerships to expedite commercialization for NCI‐funded small business entrepreneurs. Issue 6 (13th August 2021) - Connors, Brittany; Lou, Xing‐Jian; Subedee, Ashim; Zhang, Kehui; Weingarten, Michael; Narayanan, Deepa
Abstract: The National Cancer Institute's Small Business Innovation Research Development Center (NCI SBIR) provides federal research and development funding and commercialization resources to more than 400 small businesses each year developing novel technologies to prevent, diagnose, and treat cancer. Although federal funding is vital for life science startups at the early stage of development, it is often insufficient to translate the technology from discovery to commercial product. Early‐stage startups must connect to follow‐on capital and resources to bring NCI‐funded technologies to patients. Most startups face challenges in securing additional funding due to lack of access to investors and strategic partners and the ability to effectively pitch their technology. In 2015, the NCI SBIR started the Investor Initiatives program to connect funded small businesses with targeted investors and strategic partners to address the aforementioned obstacles. This program leverages an extensive network of investors and partners to conduct business‐focused reviews and provide pitch coaching. The program incentivizes earlier collaborations between NCI‐funded companies and private investors through various channels. The program has supported 117 companies from years 2016–2019 to attend 27 investor showcase events. Follow‐up surveys show that the program and the assistance offered by NCI SBIR have contributed to a total of 32 completed deals as of April 29, 2020. This paper will discuss the Investor Initiatives program and its outcomes from 2016 to 2019 and demonstrate the effectiveness of a federal program that leverages public‐private partnerships to assist portfolio companies with raising follow‐on funding to accelerate the translation of research into clinical practice.